Exercise, immune system and circadian rhythm - Boukelia, B. (Journal of Sports Medicine & Doping Studies, 2015)
The link between circadian rhythmicity and sport performance has been extensively studied with several contributing factors having been identified. These factors can be endogenous, including physiological changes such as core body temperature; and exogenous, including environmental changes such as sleep deprivation, and daily training time [5]. Identifying the cause for improved performance is often difficult because performance fluctuations can be affected by different exogenous and endogenous factors occurring at the same time of day. Athletes, coaches and event organisers can program their race events or training to target the time when athletes perform best and should consider the immunological and physiological parameters that can enhance performance.